Youth quotas and "Jurassic Park" politicians: age as a heuristic for vote choice in Tunisia's new democracy. Issue 6 (17th August 2020) - Dobbs, Kirstie Lynn
ABSTRACT: Countries that undergo a democratic transition often adopt youth quotas to ensure stability and legitimacy in the eyes of a potentially rebellious youth cohort. Tunisia followed this trend by instating a youth quota after undergoing a youth-led democratic revolution in 2011. This subsequently led to youth representing 52% of the candidates (aged 18–35) in the 2018 municipal elections. However, it has yet to be tested whether a candidate's age matters when evaluating politicians and casting a ballot in elections among Tunisian voters. This article explores the link between age and candidate evaluations which has been largely understudied in the political behaviour literature. Using an original survey experiment fielded in Tunisia, I run a series of regressions that model the relationship between several age treatments and candidate evaluations. Overall, I find that most Tunisians do not use age as a heuristic cue when evaluating political candidates running for office with the exception of the oldest voters who tend to prefer a candidate that is in their 50s. These results showcase the potential limitations of youth quotas serving as a mechanism ascertaining governmental legitimacy in the eyes of young people.